2012
DOI: 10.2190/om.64.4.e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Death Anxiety among Elderly People: A Literature Review and Empirical Investigation

Abstract: Given the growing number of elderly persons in society and concerns about their health and well-being, the aim was to review the available literature on their death anxiety, and to explore features of this experience among a small sample of older men and women in care facilities. In both the review and empirical parts of this study, components and correlates of death anxiety were investigated. The review revealed limited research focus on death anxiety among the elderly, particularly among those in institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 29 publications
6
53
1
4
Order By: Relevance
“…Abdel-Khalek et al found that, on the ASDA, Egyptian, Kuwaiti, Lebanese, Syrian, Spanish, and American women (no English women) had significant higher mean scores than men [29]. Missler et al reported that women compared to men had more fear of the death of loved ones and of the consequences of their own death on these loved ones [16]. Singh reported that women as compared with men had more death anxiety [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdel-Khalek et al found that, on the ASDA, Egyptian, Kuwaiti, Lebanese, Syrian, Spanish, and American women (no English women) had significant higher mean scores than men [29]. Missler et al reported that women compared to men had more fear of the death of loved ones and of the consequences of their own death on these loved ones [16]. Singh reported that women as compared with men had more death anxiety [33].…”
Section: Discussionmentioning
confidence: 99%
“…Missler et al revealed that Dutch elderly people who were in an assisted living facility had higher levels of fear for others and of the dying process than of fear of the unknown. The fear for important others correlated with poor somatic health; and fear of the dying process correlated with low self-esteem, small goal in life, and poor mental well-being [16]. For most of old-aged individuals who encounter death of their spouses, death anxiety increases in them.…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that education about death reduces fear of death in old age (Hayslip, Galt, & Pinder, ). However, very few intervention studies have been conducted on reducing anxiety about death and loneliness in older adults (Luanaigh & Lawlor, ; Missler et al., ; White, Gilner, Handal, & Napoli, ). Therefore, research on new interventions aimed at reducing anxiety regarding death and loneliness are necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Death anxiety is one of most important issues among this aging population since they experience the inevitability of death approaching of and it is also important for them to achieve a sense of integrity versus despair (1, 2). Due to the invariable nature of this stressful factor, elderly people are more likely to try to emotionally avoid this situation or to use philosophical or spiritual beliefs to help them to cope with these uncontrollable situations (3).…”
Section: Introductionmentioning
confidence: 99%